Exchange rate behavior of Canada, Japan, the United Kingdom and the United States - Ariff, Mohamed *; Zarei, Alireza * (Springer, 2016)
We revisit a significant research topic on exchange rate behavior by restating the test procedures with an appropriate econometric methodology to re-examine three aspects. (i) Does the inflation (price) factor affect nominal exchange rate? (ii) Do relative interest rates affect a country’s exchange rate? (iii) Do the price and interest rate effects hold if controls for non-parity factors are embedded in tests? The quarterly data series for this study are taken over 55 years. The traditional parity condition model with price and interest rate as criterion variables is extended to take into account recently-verified non-parity factors, namely trade, productivity and foreign reserves.The results affirm that both parity factors and also the non-parity factors significantly affect the exchange rates of Canada, Japan, the United Kingdom and the United States. In our view, these findings relating to four free-floating currencies help extend our knowledge on how currency behavior is consistent with parity and non-parity theorems using a relevant methodological approach in this study.